The Impact of Digital Communication and PR Models on the Sustainability of Higher Education during Crises - Ayman, Umut; Kaya, Anil Kemal; Kuruc, Ulfet Kutoglu (Mdpi, 2020)
Currently, the world is going through a pandemic, COVID-19, that affects the four pillars of organizational sustainability. At this point, institutions' sustainability depends on how they handle crisis communication. It seems that institutions that can adapt themselves to changes regarding the usage of digital communication platforms are survivors, and even winners, of this crisis. The general belief concerning education in developing countries claims that these countries are slow in adapting to technological innovations. Being a developing country, North Cyprus has a multi-cultural environment due to the presence of international students in tertiary education. This study explores how two public and two private universities maintained sustainability in higher education during COVID-19 by discussing the public relations models (PR) that they have used regarding digital communication. This study uses a qualitative content analysis and a quantitative method. The paper asserts that the effective usage of digital communication contributes to the sustainability of universities during this crisis. The findings revealed that the posts (text/image/poster) and videos these universities share are more concentrated on either press agentry or the public information model. Yet, a two-way symmetrical model that maintains dialogue within stakeholders is practiced less than the other PR models. Hence, there is a need for the universities to listen to their stakeholders not only in face to face communication but more through digital communication platforms as well.
Keywords: COVID-19 pandemic; crisis management; higher education systems; online communication; PR models